Kejadian Kanker Serviks Di Puskesmas II Denpasar Selatan Tahun 2012 - Astuti, Ni Nyoman Metri (Community Health)
Cervical cancer is a chronical disease that occurs on woman’s cervix. The mortality rate of this cancer in Indonesia is around 90 – 100 cases among 100.000 woman per year. Cases of cervical cancer can be influenced by several factors: age, age at the first sexual intercourse, multiple sex partners, number of marriage, parity, history of genital disease, and the level of knowledge.  The purpose of this research is to determine the incidence of cervical cancer among the productive-aged woman in Primary Health Care II of South Denpasar. The study design was a cross sectional descriptive study. Sampling in this study using a systematic random sampling of women in reproductive age who done a pap smear in Puskesmas II Denpasar Selatan as many as 40 WUS. Based on research conducted on WUS in the working area of the Puskesmas II Denpasar Selatan can be seen that the incidence of cervical cancer was 25%. It show the high incidence of cervical cancer, therefore early detection is needed especially women in reproductive age.